"Like Two Musketeers": Socialization beliefs about toddler's friendships among Dominican, Mexican, and African American mothers. Issue 1 (26th July 2022) - Kuchirko, Yana; Bennet, Anna; Nisanova, Linda; De Sousa, Jahnavi
Abstract: Parental ethnotheories shape socialization beliefs around childrearing more broadly, and children's friendships more specifically. While prior work has examined aspects of parental socialization of friendships among school‐aged children and adolescents, no studies have examined beliefs held around the function of friendships among ethnically diverse mothers of toddlers from low‐socioeconomic contexts. Toddlerhood marks a point in development when the concept of "friendship" gains impact and relevance due to leaps in children's social, cognitive, and motor skills, as well as children's increasing access to contexts where they organically encounter peers. Toddlerhood is also a time when caregivers may initially consider the influence of peers on their children, beliefs that could eventually guide and shift how they navigate socialization practices around friendship. In the present study, we document U.S. Dominican American, African American, and Mexican American mothers' socialization beliefs around functions of friendship for their 2‐year‐old children. We found that mothers emphasized a variety of friendship functions, including learning of social skills and morality, and communicating and experiencing emotions. A majority of mothers viewed their children's friendships as unidirectional, and framed their children as undiscerning in their engagement with social information from peers. Findings are discussed in relation to mothers' orientation to children and "childhood" via cultural and developmental beliefs.